(3EOGQI GdGFJeGfs - (3ShRGf SejQ(B, (3PjHs; (3fhQ eMehO GHQGgje hCNQhf(B, s ((3YeGf(B:s (3OGQ GdacQ(B,s, 2012)
(3GdGFJeGf GdeUQaj , GdSjhdI h GdQHMjI h GdCeGf , CfhGY GdJSgjdGJ GdGFJeGfjI , eNGWQ GdGFJeGf GdeUQaj , GOGQI GdGFJeGf , GdJMdjd GdeGdj h JMdjd GdfSH GdeGdjI dZGjGJ GdCbQGV , JMdjd fSH GdJehjd h fSH GdfTGW , GdJfHD HGdaTd GdeGdj ddTQcGJ , GdVeGfGJ , eJGHYI GdGFJeGf GdeUQaj , GOGQI GdGFJeGf aj Xd TM GdYedGJ GdGLfHjI h GNjQG QbGHI GdHfc GdeQcRj Ydi GdGFJeGf GdeUQajs
Keywords: (3GdEFJeGf GdeUQajs; (3GdEFJeGf(B- (3EOGQIs; (3Hfhc GdEFJeGfs